Removal of Cr (VI) from aqueous solutions using wheat bran - Singh K.K.; Hasan S.H.; Talat M.; Singh V.K.; Gangwar S.K. (My University, 2025)
The possible use of 'wheat bran' as novel biosorbent has been successfully demonstrated in the removal of Cr (VI) from aqueous solution. The effect of different parameters (such as contact time, sorbate concentration, pH of the medium and temperature) were investigated, and maximum uptake of Cr (VI) was attained as 310.58 mg g-1 at pH 2.0, under the initial Cr (VI) concentration of 200 mg L-1 and temperature of 40 °C. Effect of pH showed that wheat bran was not only removing aqueous Cr (VI) but also reducing it into less toxic Cr (III). When the sorption kinetics were tested with first-order reversible, pseudo-first-order, and pseudo-second-order reaction, Cr (VI) uptake process followed the pseudo-second-order rate expression. Mass transfer of Cr (VI) from bulk to the solid phase (wheat bran) was studied at different temperatures. Different thermodynamic parameters viz., ΔG°, ΔH° and ΔS° have also been evaluated, and the sorption was feasible, spontaneous, and endothermic in nature. The sorption equilibrium, when expressed by the Langmuir and Freundlich equations, indicated that the process was in compliance with Langmuir isotherm. The results of desorption studies also demonstrated that complete desorption of Cr (VI) took place at pH of 9.5. © 2009 Elsevier B.V. All rights reserved.